PENGARUH PERSEPSI DUKUNGAN ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIORAL - VS Ariyanto; Christantius Dwiatmadja; Djoko Santoso (Universitas Semarang, 2023)
The success of an institution is not only determined by many resources but also the human resources’ qualities and behaviours in the institution. Desired behaviour is the behaviour that can enhance the organizational quality that is Organizational Citizenship Behaviour (OCB). The purpose of this research is to test the impact of Perceived Organizational support, organizational commitment toward organizational citizenship behaviour (OCB) with servant leadership as a moderating variable. This research is a quantitative study using a survey with 52 respondents from Maria Mediatrix Middle School Semarang City, Central Java. Hypothesis testing uses the MRA (Moderated Regression Analysis) regression model. The result of the research shows that organizational support perception and commitment has different impact toward organizational citizenship behaviour (OCB) in Maria Mediatrix Junior High School, where the organizational commitment has significant impact while the organizational support perception is not. Servant leadership significantly affects organizational support perception relationship and organizational commitment toward organizational citizenship behaviour (OCB) in Maria Mediatrix Junior High School. Keberhasilan sebuah lembaga bukan hanya ditentukan oleh banyak sumber daya salah satunya adalah sumber daya manusia (SDM) dengan kualitas dan perilaku-perilaku yang timbul didalam lembaga tersebut. Perilaku yang diharapkan adalah perilaku yang dapat meningkatkan kualitas organisasi yaitu Organizational Citizenship Behavior(OCB). Tujuan dari penelitian ini adalah menguji pengaruh persepsi dukungan organisasi, komitmen organisasional terhadap organizational citizenship behavior (OCB) dengan servant leadership sebagai variabel moderating. Penelitian ini merupakan penelitian kuantitatif menggunakan survei dengan responden seluruh pegawai SMP Maria Mediatrix Kota Semarang, Jawa Tengah yang berjumlah 52 orang. Pengujian hipotesis menggunakan regresi model MRA (Moderated Regression Analysis). Hasil penelitian menunjukkan bahwa persepsi dukungan organisasi dan komitmen organisasi memiliki pengaruh yang berbeda terhadap organizational citizenship behavior (OCB) di SMP Maria Mediatrix, dimana komitmen organisasi memiliki pengaruh yang signifikan sementara persepsi dukungan organisasi tidak. Servant leadership secara signifikan mempengaruhi hubungan persepsi dukungan organisasi dan komitmen organisasi terhadap organizational citizenship behavior (OCB) di SMP Maria Mediatrix.